PSYCHO-PERSONOLOGICAL FACTORS AS PREDICTORS OF ACADEMIC CONFIDENCE AND MOTIVATION AMONG UNDERGRADUATES IN SOUTHWESTERN NIGERIA (2016)
Lack of academic confidence and motivation among undergraduates has become worrisome among stakeholders and educational psychologists. It often results in the inability to adjust to academic demands, socio-personal and psychological difficulties experienced by undergraduates which consequently lead to poor academic performance and high drop-out. Previous studies focused on dispositional factors with little attention on psycho-personological factors. This study, therefore, investigated psycho-personological factors (emotional intelligence, academic resilience, academic self-concept, school connectedness, gender, goal-setting, age and socioeconomic status) as predictors of academic confidence and motivation among undergraduates in Southwestern Nigeria. Self-determination theory provided the framework while correlational type of design was used. Multi-stage sampling procedure was employed to select respondents. Purposive sampling technique was used to select four states (Ogun, Ondo, Osun and Oyo) in Southwestern Nigeria. A total of 1,150 respondents were selected using proportionate sampling method from four Federal Universities (Federal University of Agriculture, Abeokuta (285), Federal University of Technology, Akure (235), Obafemi Awolowo University, Ile-Ife (310), and University of Ibadan, (320). The students who served as participants were selected across various faculties and levels. The reliability coefficient of all the variables are as follows: Academic confidence (r = 0.84), Academic motivation (r = 0.69), Emotional intelligence (r = 0.78), School connectedness (r = 0.65), Academic self-concept (r = 0.80), Academic resilience (r = 0.71), Goal-setting (r = 0.76), and Parents‘ socio-economic status (r = 0.70) scales were used for data collection. Data were analysed using descriptive Statistics, Pearson product moment correlation and Multiple regression at 0.05 level of significance. Respondents‘ mean age was 21.06 years with 57.4% females and 42.6% males. The correlation coefficient of the predictor variables are as follows: Emotional intelligence (r = 0.55), academic resilience (r = 0.60), academic self-concept (r = 0.43) and school connectedness (r = 0.43) correlated with academic confidence. Emotional intelligence (r = 0.67), academic resilience (r = 0.59), academic self-concept (r = 0.39) and school connectedness (r = 0.35) correlated with academic motivation. The variables had significant joint contribution on academic confidence (F₈, 1141) = 126.28 and academic motivation (F₈, 1141) = 132.31. The predictor variables had significant relationship with academic confidence (R = 0.69) and academic motivation (R = 0.70) accounting for 46.6% of the variance in academic confidence and 47.8% in academic motivation. The relative contributions of each of the predictor variables to academic confidence were: academic resilience (β = 0.38), school connectedness (β = 0.25), emotional intelligence (β = 0.25), parents‘ socio-economic status (β = 0.13) and academic self-concept (β = 0.06). The relative contributions of each of the predictor variables to academic motivation were: emotional intelligence (β = 0.51), academic resilience (β = 0.17) and school connectedness (β = 0.06). High emotional intelligence, academic resilience, positive academic self-concept and high school connectedness were strong facilitators of academic confidence and motivation. Counselling and educational psychologists should develop interventions rooted in these factors by training University guidance counsellors on the psychological needs of students and how to handle students‘ psychological problems to enhance academic confidence and motivation among